2011
DOI: 10.1007/s12034-011-0118-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural characteristics of titanium coating on copper substrates

Abstract: The growth characteristics of titanium films deposited on glass, silicon (100) and oxygen free high purity copper substrate using magnetron sputtering have been investigated using X-ray diffraction, electron microscopy and scratch indentation techniques. The study of interface between the titanium film and the substrate was carried out to determine coating thickness, as well as intermixing of the elements at the interface. Studies revealed that the interface is free from voids and intermixing of the film and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…No voids were observed at the thickness of the coatings between the interface of the titanium film and the substrate. The coatings on the copper substrate were even as compared to other substrates but the deposition did not show preferred orientation and intensity 8 . Graded interface was developed by depositing a thin copper layer on titanium alloy (Ti6Al4V) substrate prior to several laser cladding of cobalt on it.…”
Section: Introductionmentioning
confidence: 86%
“…No voids were observed at the thickness of the coatings between the interface of the titanium film and the substrate. The coatings on the copper substrate were even as compared to other substrates but the deposition did not show preferred orientation and intensity 8 . Graded interface was developed by depositing a thin copper layer on titanium alloy (Ti6Al4V) substrate prior to several laser cladding of cobalt on it.…”
Section: Introductionmentioning
confidence: 86%
“…EDS analysis was carried out at an accelerating voltage of 10 kV, since the characteristic X-ray energies for Ti-K a and Y-L a were only 4.5 and 1.92 keV, respectively. A Philips CM 200 analytical transmission electron microscope (ATEM) was employed for studying the cross-section of the specimen prepared manually as explained elsewhere [11]. The studies were carried out at an accelerating voltage of 200 kV and the phases were analysed by selected area diffraction (SAD).…”
Section: Methodsmentioning
confidence: 99%
“…Song et al (2007) observed that the substrate and substrate to target distance had influenced the preferential orientation and roughness of Ti grains grown by rf sputtering. Recently, Dasgupta et al (2011) studied growth of Ti films on Cu, glass and Si substrates. Polycrystalline films with fine Ti grain size were found to grow on Cu substrates.…”
Section: Introductionmentioning
confidence: 99%